Biocompatible Electrospun Polycaprolactone-Polyaniline Scaffold Treated with Atmospheric Plasma to Improve Hydrophilicity - Michela Licciardello; Gianluca Ciardelli; Chiara Tonda-Turo (Bioengineering, 2021)
Conductive polymers (CPs) have recently been applied in the development of scaffolds for tissue engineering applications in attempt to induce additional cues able to enhance tissue growth. Polyaniline (PANI) is one of the most widely studied CPs, but it requires to be blended with other polymers in order to be processed through conventional technologies. Here, we propose the fabrication of nanofibers based on a polycaprolactone (PCL)-PANI blend obtained using electrospinning technology. An extracellular matrix-like fibrous substrate was obtained showing a good stability in the physiological environment (37 °C in PBS solution up 7 days). However, since the high hydrophobicity of the PCL-PANI mats (133.5 ± 2.2°) could negatively affect the biological response, a treatment with atmospheric plasma was applied on the nanofibrous mats, obtaining a hydrophilic surface (67.1 ± 2°). In vitro tests were performed to confirm the viability and the physiological-like morphology of human foreskin fibroblast (HFF-1) cells cultured on the plasma treated PCL-PANI nanofibrous scaffolds.